Strong states, weak elections? How state capacity in authoritarian regimes conditions the democratizing power of elections. Issue 1 (January 2018) - van Ham, Carolien; Seim, Brigitte
State capacity may be a crucial factor conditioning the democratizing power of elections in authoritarian regimes. This paper develops a two-phase theory considers the different effects of state capacity on turnover in elections and democratic change after elections. In regimes with limited state capacity, manipulating elections and repressing opposition is more difficult than in regimes with extensive state capacity, rendering turnover in elections more likely in weak states. However, if the new incumbent has limited capacity to deliver public services and make policy changes after coming to power, sustainable democratic change is unlikely. Hence, state capacity is hypothesized to have a negative effect on turnover, but a positive effect on democratic change. These hypotheses are confirmed in a sample of 460 elections in 110 authoritarian regimes taking place in the period 1974 to 2012 using the Varieties of Democracy dataset. The findings suggest a need to revisit strong-state-first theories of democratization.